Health Literacy on Type 2 Diabetes Mellitus Among Patients at Primary Health Care: A Cross-Sectional Study - Nuli, Ringa Raudhatul Akbar; Aurora, Wahyu Indah Dewi; Pasai, Emildan (Scientific Of Environmental Health and Diseases, 2026)
ABSTRACT Background: Health literacy plays a pivotal role in the effective management of Type 2 Diabetes Mellitus (T2DM), influencing patients' ability to understand health information, adhere to treatment, and adopt healthy lifestyles. Limited health literacy has been associated with poor glycemic control, increased risk of complications, and higher healthcare utilization. This study aimed to assess health literacy among patients with T2DM and identify sociodemographic factors associated with health literacy in a primary health care setting in Jambi, Indonesia. Method: A cross-sectional study was conducted among 170 patients with T2DM attending Puskesmas Putri Ayu, Jambi, Indonesia, between January and March 2025. Participants were recruited using consecutive sampling. Data were collected through interviewer-administered structured questionnaires assessing sociodemographic characteristics and diabetes-related health literacy. Health literacy was categorized as poor, moderate, or good based on the total questionnaire score. Descriptive statistics, Chi-square tests, and multivariable logistic regression were used to analyze the data.. Result: Among the 170 participants, 61.8% were female and 35.3% were aged 51–60 years. Most respondents had completed secondary education (58.8%). Poor health literacy was identified in 57.6% of participants, while 30.6% demonstrated moderate health literacy and only 11.8% had good health literacy. Educational attainment, age, employment status, and family history of diabetes were significantly associated with health literacy (p < 0.05). Higher educational attainment was the strongest predictor of adequate health literacy.. Conclusion: Most patients with T2DM attending primary health care demonstrated inadequate health literacy. Strengthening patient-centered educational interventions tailored to patients' educational backgrounds and individual needs is essential to improve diabetes self-management and support better health outcomes.